Profile of Patients with Mitral Stenosis in Dr. Soetomo General Hospital, Surabaya in January 2015 – December 2017 - Nadia Mulyanti Gunawan; Raden Mohammad Budiarto; Andriati Andriati (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: The most common valvular heart disease is mitral stenosis. Mitral stenosis is an abnormality of the heart valve which causes reduced blood flow from the left atria to the left ventricle due to narrowing of mitral valve orifice during its opening motion. If the condition continues, it will result in complications. The most common complications are pulmonary hypertension, atrial fibrillation, heart failure, and stroke. Appropriate treatment for mitral stenosis may produce more favorable prognosis in these patients. Therefore, the aim of this study was to describe the profile of patients with mitral stenosis in Department of Cardiology and Vascular Medicine, Dr. Soetomo General Hospital, Surabaya from January 2015 to December 2017. It is expected that mitral stenosis can be detected earlier, thus the appropriate treatment can be administered promptly and further complications can be prevented. Methods: This study was a descriptive retrospective study with cross-sectional approach and accidental sampling method obtained from the inpatients medical records of patients diagnosed with mitral stenosis from echocardiography in Department of Cardiology and Vascular Medicine Dr. Soetomo General Hospital, Surabaya from January 2015 to December 2017. The variables were age, gender, disease severity, and the patient’s educational background. The data was processed using Microsoft Excel and IBM SPSS version 20. Results: This study obtained 41 patients who met the inclusion criteria, then the patients were categorized according to their age, gender, disease severity, and educational background. The results of the study showed that the subjects were dominated by those of productive age at 30-39 years old (39%), the most prevalent gender was female (85.4%), severe disease severity (85.4%), and educational level was from high school (85.4%). Conclusion: The majority of the patients with mitral stenosis were from productive age, female, with severe disease severity, and educational background from middle educational level (high school).